Isolation and Screening of Actinomycetes producing Antibacterial compounds from different river sediments - Abbas, Sahil; Gautam, Girendra; Gautam, Pawan Kumar (Journal of Drug Delivery and Therapeutics, 2019)
The history of antibacterial begins with the observations of Pasteur and Joubert, who discovered that one type of bacteria could prevent the growth of another. They did not know at that time that the reason one bacterium failed to grow was that the other bacterium was producing an antibiotic. Of course, in today’s common usage, the term antibiotic is used to refer to almost any drug that attempts to rid your body of a bacterial infection. The past researches indicated that huge number of antibiotics was produced by Gram +ve ike bacteria known as Actinomycetes. So we can say that among all microbes more than 50% of the known antimicrobial compounds were produced by Actinomycetes only. In our study isolation and screening of Actinomycetes was performed by using different river sediments. Soil samples was collected from river Godaveri and Krishna and stored in the U.V. and alcohol sterilized Poly bags. Soil samples was serially diluted up to 10-6 and 1 ml from each dilution was plated on different isolation media like starch Casein agar, Albumin media and YMA media, consisting of antifungal agent Nystatin 50 µg/ ml, by pour plate technique. The plates were incubated at different temperature ranges 18 0C to 28 0C upto 7-14 days. Determination of antibacterial activities of pure actinomycetes cultures of S1, S2, S3 and S4 were performed by using streak -plate method. Mueller hinton agar plates will prepared and inoculated with actinomycetes cultures by a single streak of inoculums in the center of the Petri dish and will incubated at 270C for 4 days. Later, the plates will seeded with test organisms by a single streak at a 900 angle to actinomycetes strains. Antagonism was measured by the determination of the size of the inhibition zone. The antibacterial activity of compound was tested against different gram +ve and Gram –ve by the standard disc diffusion method and cup plate method. Standard streptomycin was used for comparison of the antibacterial activity.